Development of Multiple Skill Laboratory Activity Model (MSLAM): An Instrument to Improve 21st Century Skills of Student - Adam Malik; Mujib Ubaidillah (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
This study aims to develop a Multiple Skills Laboratory Activities Model (MSLAM), which can train and develop students' 4C skills (critical, creative, communication, and collaboration) through laboratory activities. This study used the Research and Development method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. There are 70 students ─ 18 males and 52 females ─ who participate in this research. The research instrument consisted of expert validation sheets, tests, and performance assessments. The Likert and Guttmann scale analyzed the MSLAM validation sheet. The test results were analyzed using a normalized gain score <g>, and the performance assessment was analyzed using a Likert scale. The results of expert validation show that MSLAM is very feasible to be implemented in laboratory activities. The test results showed an increase in students' critical and creative thinking skills in the MSLAM group were greater than in the Higher Order Thinking Laboratory/HOT Lab group. Students' communication and collaborative skills in the MSLAM group were greater than in the HOT Lab group. These results indicate that the MSLAM model developed can improve students' 4C skills through laboratory activities. Thus, the MSLAM can be applied in physics learning to develop students' various higher-order thinking skills.